2018
DOI: 10.1186/s13293-018-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the traumatic stress response: the role of adult gonadal hormones

Abstract: BackgroundOur previous study revealed that adult female rats respond differently to trauma than adult males, recapitulating sex differences in symptoms of post-traumatic stress disorder (PTSD) exhibited by women and men. Here, we asked two questions: does the female phenotype depend on (1) social housing condition and/or (2) circulating gonadal hormones?MethodsFor the first study, the effects of single prolonged stress (SPS) were compared for females singly or pair-housed. For the second study, adult male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 59 publications
3
43
1
Order By: Relevance
“…For the females, one interpretation of these data is that recruitment of coping strategies such as defensive digging protects against lasting behavioral responsivity in hyperarousal and anxiety-like tests. While a previous study has reported females show hypo-responsiveness of the acoustic startle response following traumatic stress exposure [48] and predator odor stress [25], it is possible that by providing female rats the opportunity to engage in different behavioral coping strategies (i.e., bedding for digging), we were able to separate specific type of responders that represent susceptibility or resiliency to developing lasting behavioral changes in arousal. Conversely, the lack of change in hyperarousal in male rats exposed to TMT remains unclear, but future work could manipulate different startle intensity or examine prepulse inhibition to further dissect this behavioral difference.…”
Section: Discussionmentioning
confidence: 84%
“…For the females, one interpretation of these data is that recruitment of coping strategies such as defensive digging protects against lasting behavioral responsivity in hyperarousal and anxiety-like tests. While a previous study has reported females show hypo-responsiveness of the acoustic startle response following traumatic stress exposure [48] and predator odor stress [25], it is possible that by providing female rats the opportunity to engage in different behavioral coping strategies (i.e., bedding for digging), we were able to separate specific type of responders that represent susceptibility or resiliency to developing lasting behavioral changes in arousal. Conversely, the lack of change in hyperarousal in male rats exposed to TMT remains unclear, but future work could manipulate different startle intensity or examine prepulse inhibition to further dissect this behavioral difference.…”
Section: Discussionmentioning
confidence: 84%
“…Administration of PPT impairs the ability of dexamethasone to suppress the diurnal rise and restraint stress-induced release of ACTH and CORT [158]. It is important to note that while androgens are capable of producing these effects via further metabolism and binding of ERα, systemic T generally suppresses stress-induced HPA axis responses and increases negative feedback on the HPA axis [16,159]. This suggests that interactions with other gonadal steroid hormone receptors might negate or diminish any HPA axis enhancing effects of ERα.…”
Section: Estrogen Receptor Alpha Hpa Axismentioning
confidence: 99%
“…In rats, the use of a single prolonged stress protocol, which models post‐traumatic stress disorder, oppositely regulated GR number in the PVN and the hippocampus of males and females (Pooley et al, ). Stress up‐regulated GR expression in the PVN of male rats but down‐regulated it in the hippocampus, whereas the opposite occurred in stressed females.…”
Section: Sex Differences In the Gr/mr Systemmentioning
confidence: 99%